Stem Cell Based Models in Congenital Hyperinsulinism – Perspective on Practicalities and Possibilities - Lithovius, Väinö; Otonkoski, Timo (Frontiers in Endocrinology, 2022)
Congenital hyperinsulinism (CHI) is a severe inherited neonatal disorder characterized by inappropriate insulin secretion caused by genetic defects of the pancreatic beta cells. Several open questions remain in CHI research, such as the optimal treatment for the most common type of CHI, caused by mutations in the genes encoding potassium-sensitive ATP channels, and the molecular mechanisms of newly identified CHI genes. Answering these questions requires robust preclinical models, particularly since primary patient material is extremely scarce and good animal models are not available. In this short review, we explain why pluripotent stem cell derived islets present an attractive solution to these issues and outline the current progress in stem-cell based modeling of CHI. Stem cell derived islets enable the study of molecular mechanisms of CHI and the discovery of novel antihypoglycemic drugs, while also providing a valuable model to study the biology of variable functional beta cell states.